MANAJEMEN KURIKULUM PENDIDIKAN BAHASA ARAB DI AL- HIKMAH BOARDING SCHOOL JATIM - Isbah, Faliqul; Abdallah, Fariz Abshar; Rizkiyati Saniyyah, Saila; Adji, M. Arsalrifqi; Farkhanah, Aniq (ELOQUENCE : Journal of Foreign Language, 2024)
Background: Arabic education in boarding schools still faces a gap between the existing curriculum and technology utilization. Many schools have not optimized the Learning Content Management System (LCMS), which hinders the effectiveness of language learning and produces insufficient outcomes to guide students toward excellence. Purpose: his study aims to describe (1) Management of Arabic Curriculum, (2) Digital Technology Curriculum Based on LCMS, (3) Implementation of Arabic Language Learning Based on LCMS, (4) Evaluation of Arabic Language Learning Based on LCMS, and (5) Output of Arabic Curriculum Management Based on LCMS in Boarding Schools. Method: This research uses a qualitative approach with a descriptive study design to understand the application of LCMS in managing the Arabic curriculum at SMA Al-Hikmah in East Java. Data was collected through interviews, observations, and documentation. The data was analyzed using Miles and Huberman's analytical model, which includes data reduction, presentation, and conclusion. Triangulation was performed to ensure data validity. Results and Discussion: The results indicate that curriculum management at SMA Al-Hikmah comprises an Innovative Curriculum and Digital Technology, integrating LCMS for material access. Learning is conducted through e-learning and applications, with evaluations based on data analytics encompassing various assessments. The output includes improved Arabic language competence and skills in IT, research, and the Quran. Conclusions and Implications: This study emphasizes that an LCMS-based curriculum can enhance Arabic language competence and character development in students. The implications provide new insights for developing curriculum management in boarding schools, helping students become more character-driven, high-achieving, and competitive on a global scale.